Security Practices and the Production of Center–Periphery Figurations in Statebuilding. Issue 4 (November 2018) - Bonacker, Thorsten
In this article, I examine the role security plays in creating a socioterritorial order in statebuilding policies. I argue that security contributes to the creation of center–periphery asymmetries, for example, through the portrayal of the center as threatened by a dangerous periphery or the periphery as disloyal and untrustworthy. In particular, I explore how security practices work in two distinct center–periphery figurations: in internal colonization, where a specific population, located within a dominant power, is subordinated; and in international intervention, where a society is internationally ruled. The article incorporates the literature on internal colonialism and international intervention from a critical security studies perspective to show how security functions as a mode of governing by creating specific center–periphery figurations in statebuilding. The overall aim is to provide a new theoretical perspective by intertwining critical security and postcolonial studies and to stimulate empirical research on the function of security as a principle of socioterritorial ordering.